Optimalisasi Ko-Pirolisis Campuran Eceng Gondok dan Batubara Muda Terhadap Produksi Bio-Oil, Gas, dan Char - Sabitah, A'yan; Noor Ardiyat, Ichwan; Misbachudin, Misbachudin (Infotekmesin, 2025)
One of the abundant biomass resources in Indonesia is water hyacinth, which can be converted into energy through pyrolysis. This research explores the effect of temperature on the co-pyrolysis process of a mixture of water hyacinth and young coal to produce bio-oil, gas, and char. The method used is pyrolysis with temperature variations on the mixture of water hyacinth and young coal in a batch reactor. The testing was conducted at a temperature of 400°C with various compositions of water hyacinth and coal mixtures, and the resulting products in the form of bio-oil, gas, and char were then measured to determine the yield. The research results show that in the pyrolysis of pure water hyacinth, gas production reaches 120 grams, bio-oil 108 grams, and char 72 grams. The addition of coal up to 30% increases char production to 113 grams, but decreases gas production to 94 grams and bio-oil to 87 grams. The gas produced is dominated by methane (67.315%) in a mixture of 70% water hyacinth and 30% coal, while hydrogen reaches 33.721% in pure water hyacinth.